Business Communication Strategy In An Effort To Increase Consumer Buying Interest At Aura Cafe 2 Ciputat Timur - Salman, Dhani; Darmawanti, Darmawanti; Depina, Depina; Annisya, Raden Roro; Saktisyahputra, Saktisyahputra (Jurnal Ilmu Sosial Mamangan, 2025)
Study This aiming For analyzing communication strategies business in increase interest buy consumers at Aura Cafe 2 Ciputat Timur. MSMEs, especially in industry culinary, facing challenge increasingly competitive tight. Through method descriptive qualitative, research This find that effective communication is very important in build strong relationship with customers. Social media plays a role as tool main in promotion and interaction with consumers. Research results show that with implementing a comprehensive communication strategy, Aura Cafe 2 can increase visibility, attractive customer new, and maintain existing customers there is. Research This give recommendation For evaluation periodic towards communication strategy use reach objective desired business.